2021
DOI: 10.1007/s10518-021-01234-6
|View full text |Cite
|
Sign up to set email alerts
|

Force–displacement relationship modelling of masonry infill walls with openings in hinged steel frames

Abstract: The seismic behaviour of masonry infilled frames has attracted extensive attention from researchers, and it was found that infills normally experienced a diagonal compression under lateral loading. The infill was therefore assumed as an equivalent diagonal strut in structural response estimations of infilled frames, and a force-displacement curve was adopted to describe the mechanical properties of the strut. However, in the development of the force-displacement relationship of infills, the influences of infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…[66][67][68] The principal reason is that the introduction of door openings disrupts the working mechanism and force transmission mechanism of these infill systems. 69 As a result, the activation of the detrimental multiple-diagonal strut effect, which is dispersed surrounding the door openings, leads to escalated damage to both the infill walls and door openings. 70,71 Notably, compared to the previous study shown in reference, 70 this study more focuses on the comprehensive comparisons between the cyclic behavior of the proposed novel infill wall and the traditional infill wall with a door opening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[66][67][68] The principal reason is that the introduction of door openings disrupts the working mechanism and force transmission mechanism of these infill systems. 69 As a result, the activation of the detrimental multiple-diagonal strut effect, which is dispersed surrounding the door openings, leads to escalated damage to both the infill walls and door openings. 70,71 Notably, compared to the previous study shown in reference, 70 this study more focuses on the comprehensive comparisons between the cyclic behavior of the proposed novel infill wall and the traditional infill wall with a door opening.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, supplementary fixtures are often deemed necessary to safeguard both the infill wall and door opening 66–68 . The principal reason is that the introduction of door openings disrupts the working mechanism and force transmission mechanism of these infill systems 69 . As a result, the activation of the detrimental multiple‐diagonal strut effect, which is dispersed surrounding the door openings, leads to escalated damage to both the infill walls and door openings 70,71 .…”
Section: Introductionmentioning
confidence: 99%